2023
DOI: 10.3390/rs15133281
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval Consistency between LST CCI Satellite Data Products over Europe and Africa

Abstract: The assessment of satellite-derived land surface temperature (LST) data is essential to ensure their high quality for climate applications and research. This study intercompared seven LST products (i.e., ATSR_3, MODISA, MODIST, SLSTRA, SLSTRB, SEVIR2 and SEVIR4) of the European Space Agency’s (ESA) LST Climate Change Initiative (LST_cci) project, which are retrieved for polar and geostationary orbit satellites, and three operational LST products: NASA’s MODIS MOD11/MYD11 LST and ESA’s AATSR LST. All data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Numerous studies have noted discrepancies between LST acquired at essentially the same time from both geostationary and polar-orbiting platforms (e.g., Pérez-Planells et al, 2023). Nighttime LST products exhibit good agreement across various viewing configurations, whereas daytime observations have discrepancies attributed to the influence of shadows and temperature gradients within the landscape cover .…”
Section: Distribution Of Szac Coefficient and Its Physical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have noted discrepancies between LST acquired at essentially the same time from both geostationary and polar-orbiting platforms (e.g., Pérez-Planells et al, 2023). Nighttime LST products exhibit good agreement across various viewing configurations, whereas daytime observations have discrepancies attributed to the influence of shadows and temperature gradients within the landscape cover .…”
Section: Distribution Of Szac Coefficient and Its Physical Implicationsmentioning
confidence: 99%
“…demonstrated a difference of approximately ±1 K between LST products from the AVHRR sensor onboard Metop polar-orbiting satellites and the Spinning Enhanced Visible and Infrared Imager (SEVIRI) onboard the MSG geostationary platform. Pérez-Planells et al (2023) reported that Terra-and Aqua-MODIS LST products (i.e., MOD11 and MYD11, respectively) were around 2 K cooler than the LST datasets from the European Space Agency's Climate Change Initiative (ESA CCI) across all land cover classes. Similarly, found MYD11 LST generally showed lower values than their SW algorithm-retrieved Himawari-8 LST over southeast China and Australia.…”
Section: Introductionmentioning
confidence: 99%